2020
DOI: 10.1021/acs.analchem.0c01707
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Real-Time Simultaneous Examination of Drug Kinetics at Two Separate Locations Using Boron-Doped Diamond Microelectrodes

Abstract: Methylcobalamin, which is used for the clinical treatment of patients with neuropathy, can have an impact on the sensorineural components associated with the cochlea, and it is possible that the auditory threshold in a certain population of patients with deafness may be recovered. Nonetheless, it remains uncertain whether the action site of methylcobalamin is localized inside or outside the cochlea and which cellular or tissue element is targeted by the drug. In the present work, we developed a method to reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…These findings suggest that methylcobalamin possibly reaches compartments other than perilymph and exerts a pharmacological effect. Hanawa et al, 2020). Methylcobalamin (10 mg/kg) was injected into the left external jugular vein at 30 min (filled arrowhead) after the onset of the recording.…”
Section: In Vivo Electrochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…These findings suggest that methylcobalamin possibly reaches compartments other than perilymph and exerts a pharmacological effect. Hanawa et al, 2020). Methylcobalamin (10 mg/kg) was injected into the left external jugular vein at 30 min (filled arrowhead) after the onset of the recording.…”
Section: In Vivo Electrochemistrymentioning
confidence: 99%
“…These results indicate that our microsensing system can simultaneously monitor pharmacokinetics and pharmacodynamics in a live cochlea. Additionally, we constructed a different system, composed of two BDD microelectrodes, and examined methylcobalamin concentration in separate targets ( Hanawa et al, 2020 ). This cobalamin derivative is often administered to patients with SNHL ( Wang et al, 2013 ).…”
Section: In Vivo Electrochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…increasing year by year and several review articles and books on diamond-based electrodes have now been published. [1][2][3][4][5][6][7][8][9][10] For the last 20 years, our research group have reported not only fundamental studies on BDD, but also on several novel electrochemical applications such as electrochemical sensors (including biomedical), [11][12][13][14][15][16][17][18] electrochemiluminescence, [19][20][21][22] and electrochemical organic synthesis. [23][24][25] These applications are due to the unique properties of BDD electrodes, and they could not be achieved using conventional electrodes.…”
mentioning
confidence: 99%